Research and development, profits, and firm value: A structural estimation - Missaka Warusawitharana (Quantitative Economics, 2015)
This study presents a model in which firms invest in research and development (R&D) to generate innovations that increase their underlying profitability and invest in physical capital to produce output. Estimating the model using a method of moments approach reveals that R&D expenditures contribute significantly to profits and firm value. The model also captures variation in R&D intensity, profits, and firm value across R&D-intensive industries. Counterfactual experiments suggest that changes in the distribution of firms in the economy may, over the long run, mitigate tax policy changes designed to encourage R&D expenditures.
Keywords: 330; Research and development; structural estimation; firm dynamics; policy evaluation